PENYEBARAN SISTEM PERTAHANAN AMERIKA SERIKAT: TINJAUAN MELALUI PERSPECTIVE RATIONAL-CHOICE - Miftah Farid Darussalam; Muhammad Fikri Amra (Universitas Jenderal Ahmad Yani, 2025)
This study examines the deployment strategy of United States defense systems to allied nations through the lens of rational-choice theory. Employing rational actor theory framework and non-offensive defense concepts, this research analyzes US foreign policy in distributing defensive weapons systems across European, Asian, and Middle Eastern regions. The analysis reveals that the US implements this policy based on cost-benefit calculations encompassing military, economic, and political interests. Findings indicate that defense system deployment is driven by counter-terrorism objectives, economic interest protection, and maintenance of global political influence. Allied nations accept this cooperation due to shared security interests and the necessity for advanced defense capabilities against regional threats. This policy reflects rational decision-making where perceived benefits outweigh potential costs for all involved parties. The study demonstrates how mutuality of interests, shadow of future considerations, and the number of actors involved shape cooperative security arrangements in contemporary international relations.